2018
DOI: 10.1007/s00464-018-6575-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after elective colon cancer surgery: an observational study from the Norwegian registry for gastrointestinal and HPB surgery, NoRGast

Abstract: Background To describe the real burden of major complications after elective surgery for colon cancer in Norway, and to assess which predictors that are significantly associated with the short-term outcome. Methods An observational, multi-centre analysis of prospectively registered colon resections registered into the Norwegian Registry for Gastrointestinal Surgery, NoRGast, between January 2014 and December 2016. A propensity score-adjusted subgroup analysis for surgical access groups was attempted, with lapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
3
7
1
1
Order By: Relevance
“…ASA-scores were grouped into low ASA-scores (scores 1-2) and high ASA-scores (scores 3-4). ECOG-scores were dichotomized into low ECOG-score (0-1) and high ECOG-score (2)(3)(4). Severe pulmonary disease was defined as having FEV1 < 50% or a vital capacity < 60% of predicted values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ASA-scores were grouped into low ASA-scores (scores 1-2) and high ASA-scores (scores 3-4). ECOG-scores were dichotomized into low ECOG-score (0-1) and high ECOG-score (2)(3)(4). Severe pulmonary disease was defined as having FEV1 < 50% or a vital capacity < 60% of predicted values.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion to open access was followed by higher rates of major complications, reoperations, longer LOS, higher rates of positive CRM, and tumor-near bowel-perforation. Higher rates of complications have been associated with conversion of laparoscopic colon cancer resections in several studies [3][4][5][6][7]. In a study with prospectively collected data of 470 patients who underwent laparoscopic colorectal resections including 192 rectal resections, postoperative complication rates were significantly higher for patients who experienced conversion to open access, with a rate of 56.1% versus 16.8% when resections were completed laparoscopically [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study in two Norwegian hospitals, the presence of surgical complications in patient administrative systems was found to have a sensitivity and specificity of 56 and 95 per cent respectively, and 76 and 65 per cent after exclusion of complications present on admission. A medical registry study found a 14·0 per cent rate of major complications after elective colonic cancer surgery in Norway. This corresponds well with the finding of a 20·2 per cent rate of complications with Clavien–Dindo grade III–IV for all gastrointestinal operations.…”
Section: Discussionmentioning
confidence: 99%